(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
the word constructive with the help of the teacher, the organizers of the business and the other side carries. Shuningdek, establish a mutual relationship with the students, will make contact with them. All full and clear picture of the word because it activates more of the education process in the formation of assistance, education function, active perception, and will help you to understand the depth.